The World Trade Organization (WTO) Rules and Regulation: A Threat or Promise to Indonesia’s Agricultural Policy? - Arfin Sudirman (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2017)
The WTO is a formally structured organization whose rules are legally binding on its member states. The organization provides a framework for international trade law. Indonesia has been part of WTO membership since 1995. However, the agreement does not always compatible with domestic economic policy particularly on agricultural sector. This article aims to understand the possibility of Indonesia’s economic development particularly on agriculture follow WTO’s policy track into greater prosperity. By using qualitative method, this article concluded that in a broad economic securitization, agricultural products actually have been neglected by securitizing actors (Indonesian government) to fulfill their basic needs in balancing the inequalities between rich and poor. Furthermore, Indonesia’s traditionalist economic method is incompatible with neoliberalist’s economic principle due to social and demographic diversity.